λ-Commuting of bounded linear operators on ultrametric Banach spaces and determinant spectrum of ultrametric matrices - Ettayb Jawad (Topological Algebra and its Applications, 2023)
In this article, we study the λλ -commuting of bounded linear operators on ultrametric Banach spaces and the determinant spectrum of ultrametric matrices. We discuss some properties of λλ -commuting of bounded linear operators and the determinant spectrum of ultrametric matrices. Finally, we provide some examples to support our work.